NATURAL LANGUAGE PROCESSING-BASED BLENDED LEARNING IN THE EFL FLIPPED CLASSROOM: A CONCEPTUAL FRAMEWORK AND PROPOSED DESIGNS - Baskara, Risang (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The use of Natural Language Processing (NLP) in the English as a Foreign Language (EFL) flipped classroom has the potential to support blended learning and enhance learner autonomy and language development. However, there is a need for more research on the use of NLP in the EFL flipped classroom. This paper addresses this research gap by proposing a conceptual framework for using NLP in the EFL flipped classroom and a set of proposed designs and activities incorporating NLP to enhance learner autonomy and language development. This paper aims to provide a conceptual framework for using NLP in the EFL flipped classroom and propose a set of designs and activities incorporating NLP to enhance learner autonomy and language development. This paper's methodology involves reviewing the literature on NLP and the flipped classroom and developing a conceptual framework and proposed designs and activities. The product of this paper is a conceptual framework for using NLP in the EFL flipped classroom to support blended learning and a set of proposed designs and activities that incorporate NLP to enhance learner autonomy and language development. This paper concludes that NLP has the potential to support blended learning and enhance learner autonomy and language development in the EFL flipped classroom. However, further research is needed to evaluate these approaches' effectiveness and identify best practices for using NLP in the EFL flipped classroom.